PEMANTAUAN KUALITAS AIR ONLINE DAN REALTIME DI INTAKE PDAM TAMAN KOTA CENGKARENG DRAIN DKI JAKARTA - Wahjono, Heru Dwi (Jurnal Air Indonesia, 2009)
The need for clean water in big cities is very dependent on water supply by water companies (PDAM). The increasing demand for clean water in big cities is proportional to the increasing of number population and industry, but not comparable to the clean water supply and quality of raw water available. PDAM has made various efforts to improve the quality of clean water services to the community. One of the effort is to improve the performance of water treatment plant (WTP). To support the improvement of the performance of WTP, required water quality monitoring at the intake location in use. This paper discusses the online and realtime water quality monitoring at the water intake location using a multi-probe digital sensor and GSM technology. This observation data is used as a comparative data analysis of laboratory data on raw water source PDAM Taman Kota (Cengkareng Drain).Ã‚Â Keywords: air baku air minum, intake PDAM Taman Kota Cengkareng Drain, pemantuan kualitas air, multi probe digital sensor, teknologi online monitoring, Water Treatment Plant